A complex multi-metallic vanadium-titanium magnetite functional material processing method and electromagnetic wave absorbing powder functional material

By regulating the multimetal components and a one-step roasting process, complex multimetallic vanadium titanium magnetite is converted into wave absorbing powder, solving the problems of high energy consumption and high pollution in the smelting process of vanadium titanium magnetite, and achieving efficient resource utilization and high value-added electromagnetic wave absorption material preparation.

CN115413217BActive Publication Date: 2025-04-18ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211158643.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-22
Publication Date
2025-04-18
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

In the prior art, complex multimetallic vanadium titanium magnet ore smelting has high energy consumption, high pollution, long process, and low element recovery rate, making it difficult to achieve resource utilization.

Method used

The complex multimetallic vanadium titanium magnetite is used as the main raw material. By regulating the multimetallic components and a one-step roasting process, the functional materials of vanadium titanium magnetite are directly converted into wave absorbing powder products, achieving high-value utilization of the entire component.

Benefits of technology

It has realized the efficient value-added processing of vanadium titanium magnetite, and prepared electromagnetic wave absorption powder functional materials with good wave absorption performance, which solved the problem of resource utilization in the existing technology, and has a simple process, low cost and high added value.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for processing a complex multi-metallic vanadium-titanium magnetite functional material and an electromagnetic wave absorbing powder functional material. A mixed powder containing magnetite and ilmenite concentrates and a manganese source, a calcium source, a strontium source and a barium source is preheated, roasted, cooled and finely ground in sequence to obtain an electromagnetic wave absorbing powder functional material with excellent wave absorbing performance, which can be used as a high-quality raw material for bulk electromagnetic wave shielding building materials. The method has the characteristics of low cost and high output, and is conducive to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electromagnetic wave absorbing powder functional material, in particular to an electromagnetic wave absorbing powder functional material comprising components such as iron-manganese-vanadium-strontium-barium composite ferrite and orthotitanate, and also to a method for preparing the electromagnetic wave absorbing functional material by roasting a complex multi-metallic vanadium-titanium magnetite as a main material and adding auxiliary materials such as ilmenite concentrate, a manganese source, a calcium source, a strontium source, and a barium source, belonging to the field of mineral metallurgical material processing. Background Art

[0002] Vanadium-titanium magnetite is a symbiotic composite ore with multiple valuable elements such as iron, vanadium, and titanium. It is also an important vanadium and titanium resource and a mineral resource widely distributed in the world. Among them, China, South Africa, Russia, Canada, New Zealand, Indonesia and other countries are the main distribution countries. Vanadium-titanium magnetite is also recognized as one of the difficult-to-smelt minerals in the world, and its comprehensive utilization is difficult. Up to now, there are two main processes for smelting vanadium-titanium magnetite: traditional blast furnace process and non-blast furnace process. Among them, the non-blast furnace process is mainly the rotary kiln direct reduction + electric furnace smelting process in New Zealand and South Africa, which is the most mature.

[0003] At present, the main companies that use blast furnace smelting technology to process vanadium-titanium magnetite are Panzhihua Iron and Steel and Chengde Iron and Steel in China, Chusov Steel Company and Nizhny Tagil Steel Company in Russia. The blast furnace smelting process has many advantages, such as mature and reliable technology, high production efficiency, and the ability to achieve large-scale utilization of vanadium-titanium magnetite. Since the blast furnace smelting process requires appropriate slag viscosity to ensure the permeability and slag fluidity in the furnace, about 30% of ordinary iron ore is usually added to the raw materials entering the furnace, and the TiO2 content in the formed blast furnace slag is usually not more than 20-25%. The titanium extraction process technology of this high-titanium blast furnace slag is relatively difficult, and there is currently no effective utilization technology; therefore, the blast furnace smelting process only utilizes the iron and vanadium resources in the vanadium-titanium magnetite, and the final comprehensive recovery rate of vanadium is usually not higher than 60%, and a considerable amount of vanadium is not effectively recovered. In addition, the system and equipment configuration of the blast furnace smelting process are complex, the process energy consumption is high, and the pollutant emissions are large. In the context of practicing green development and promoting the construction of ecological civilization, the blast furnace smelting process faces great environmental and resource pressures.

[0004] There are many methods for processing vanadium-titanium magnetite by non-blast furnace smelting process, mainly pre-reduction-electric furnace smelting process and direct reduction-grinding process. The principle of pre-reduction-electric furnace smelting process is to perform pre-reduction through equipment and deep reduction in the electric furnace to achieve the separation of metallic iron melting. According to the classification of reduction equipment, it mainly includes: rotary hearth furnace coal-based direct reduction-electric furnace smelting smelting process, rotary kiln direct reduction-electric furnace smelting process, and vertical furnace coal-based direct reduction-electric furnace smelting vanadium-titanium magnetite smelting process. The rotary kiln direct reduction-electric furnace smelting process is to directly reduce the rotary kiln and then perform deep reduction and smelting in the electric furnace to obtain vanadium-containing molten iron and molten titanium slag; the vanadium-containing molten iron is blown with oxygen to extract vanadium in the molten iron ladle to obtain vanadium slag, and the comprehensive recovery rate of vanadium in the final vanadium slag is usually 70-80%. However, as a direct reduction device, the rotary kiln heats the materials in the furnace by high-temperature flames and flue gas. The oxidizing atmosphere and reducing atmosphere in the furnace cannot be effectively isolated, and the materials in the furnace rely on the rotation of the kiln body to achieve migration. Due to the inherent deficiencies of this process, the product quality is unstable and the energy consumption is too high. In addition, since the kiln body is prone to ring failure, the equipment operation rate is usually low. In addition, since the metallization rate of iron in the materials discharged from the rotary kiln is usually no more than 80%, the electric furnace smelting process not only undertakes the melting function but also undertakes a heavier reduction task, so the electric furnace smelting consumes a lot of electricity. The direct reduction-grinding process is to reduce vanadium-titanium magnetite ore to sponge iron (direct reduced iron) at a temperature lower than the melting temperature, vanadium and titanium enter the slag phase, and the vanadium-titanium slag is further extracted to achieve the purpose of separating iron, titanium and vanadium. In order to achieve complete reduction in the solid state, tunnel kiln production is often used, and production capacity is subject to certain restrictions.

[0005] How to achieve the comprehensive utilization of vanadium-titanium magnetite has always been a major problem. Whether it is the titanium in the blast furnace method that enters the slag and cannot be recycled, or the phenomenon that titanium and iron cannot be effectively separated in the non-blast furnace method, it will make the comprehensive utilization of vanadium-titanium magnetite resources difficult. In addition to being used to produce metals, polymetallic vanadium-titanium magnetite can also be used directly to make materials. The conventional utilization route of vanadium-titanium magnetite resources is mainly to prepare high-purity metal materials and inorganic non-metallic materials through beneficiation, purification, ultrafine powder, modification, processing and other processes for industrial product manufacturing. However, the preparation of high-purity raw materials has the disadvantages of complex processes, high pollution, high energy consumption and low efficiency. If low-cost, bulk and complex polymetallic vanadium-titanium magnetite is directly used as raw material, and its basic characteristics of being rich in metal components with potential wave absorption functions are utilized, high-value-added functional materials can be directly prepared through the short process of "resource material integration", this process is more reasonable, more scientific, more economical and more environmentally friendly. Exploring new ideas to achieve the short process, low carbon and functional transformation from complex and difficult-to-select mineral resources to materials is of great significance to the high-value utilization of minerals. Therefore, using vanadium-titanium magnetite to prepare mineral-based functional materials is an important way to increase the value of polymetallic vanadium-titanium magnetite. Summary of the invention

[0006] In view of the technical problems in the prior art such as high energy consumption, high pollution, long process and low element recovery rate in the pyrometallurgical smelting of complex polymetallic vanadium-titanium magnetite, the first purpose of the present invention is to provide a method for directly processing complex polymetallic vanadium-titanium magnetite into functional materials. The method uses complex polymetallic vanadium-titanium magnetite as the main raw material, and through simple regulation of the polymetallic components and a one-step roasting process, the complex polymetallic vanadium-titanium magnetite functional material can be directly converted into an absorbing powder product, thereby achieving high-value utilization of all components of the vanadium-titanium magnetite, and solving the technical problem that the prior art is difficult to utilize complex polymetallic vanadium-titanium magnetite as a resource.

[0007] Another object of the present invention is to provide an electromagnetic wave absorbing powder functional material with good wave absorbing performance, which can be widely used in electromagnetic wave shielding building materials.

[0008] In order to achieve the above technical objectives, the present invention provides a method for processing complex multi-metallic vanadium-titanium magnetite functional materials, which comprises preheating, roasting, cooling and fine grinding a mixed powder containing vanadium-titanium magnetite and ilmenite concentrate with a manganese source, a calcium source, a strontium source and a barium source in sequence to obtain an electromagnetic wave absorbing powder functional material.

[0009] The technical solution of the present invention combines vanadium-titanium magnetite, ilmenite concentrate, manganese source, calcium source, strontium source and barium source for high-temperature solid-phase reaction. In the high-temperature solid-phase reaction, the original mineral phases of ferro-titanium magnetite and ilmenite concentrate are decomposed to generate stable composite ferrite, manganese titanate and silicate phases, which constitute electromagnetic wave absorbing powder functional materials. Among them, vanadium, strontium, barium, manganese and iron are mainly converted into composite ferrite, titanium is mainly converted into orthotitanate phase, and impurities in minerals are mainly converted into silicates.

[0010] As a preferred solution, the mixing ratio of vanadium-titanium magnetite, ilmenite concentrate, manganese source, calcium source, strontium source and barium source in the mixed powder satisfies: the mass ratio of (V+Sr+Ba+Mn) / Fe is between 0.55 and 0.85; the mass ratio of Ti / Mn is between 0.65 and 1.0; the mass ratio of CaO / SiO2 is between 0.5 and 0.8; the mass percentage of total iron is not less than 45%. The present invention can adjust the generation of composite ferrite and manganese titanate with wave absorbing function during the roasting process and eliminate the adverse effects of impurity elements on product performance by strictly controlling the ratio of each component in the mixed powder. The mass ratio of (V+Sr+Ba+Mn) / Fe and Ti / Mn is controlled within the preferred range, and the composite ferrite and manganese titanate formed have good electromagnetic wave absorption performance. At the same time, by adjusting the mass ratio of CaO / SiO2, the amount of liquid phase in the roasted agglomerate and the interface properties of the local liquid phase can be adjusted. Impurity elements such as quartz will generate a low-melting silicate liquid phase, and impurities will not enter the lattice of ferrite and manganese titanate, thereby ensuring the high wave absorption performance of the multi-phase functional material. Therefore, by controlling the ingredient ratio, the transformation of multi-metal component functional materials in complex and difficult-to-select vanadium-titanium magnetite can be achieved, and a multi-phase wave absorption functional material with excellent performance can be prepared.

[0011] As a preferred solution, the fineness of the mixed powder satisfies that the mass percentage of the -325 mesh particle size is not less than 95%. The mixed powder of the present invention can be made by finely grinding the vanadium-titanium magnetite and ilmenite concentrate with solid raw materials such as manganese source, calcium source, strontium source and barium source respectively and then compounding them in proportion, or first compounding the solid powders in proportion and then compounding them. By controlling the mixed powder within an appropriate particle size range, high-temperature solid-phase reaction is facilitated.

[0012] As a preferred embodiment, the manganese source includes at least one of manganese carbonate, manganous oxide, manganese oxalate and manganese dioxide.

[0013] As a preferred embodiment, the calcium source includes at least one of calcium carbonate, calcium oxide, calcium oxalate and calcium hydroxide.

[0014] As a preferred solution, the strontium source includes at least one of strontium hydroxide, strontium oxide, and strontium oxalate.

[0015] As a preferred solution, the barium source includes at least one of barium hydroxide and barium oxide.

[0016] The manganese source, calcium source, strontium source and barium source used in the present invention are all common commercial raw materials and are analytically pure raw materials.

[0017] As a preferred solution, the preheating condition is: preheating for 10 to 60 minutes at a temperature of 600° C. to 950° C. under a nitrogen and / or inert gas atmosphere. Preheating under the preferred temperature conditions is mainly to achieve the decomposition of manganese source, strontium source, barium source, calcium source, etc. to generate highly active oxides, which is beneficial to the high-temperature solid phase reaction in the subsequent roasting process.

[0018] As a preferred solution, the calcination conditions are: calcination for 30 to 240 minutes at a temperature of 1200°C to 1350°C in an air atmosphere. When calcined at a high temperature of 1200°C to 1350°C, solid phase reaction mainly occurs, and oxides such as iron, manganese, vanadium, strontium, and barium react to form composite ferrites, while titanium, manganese, and the like generate orthotitanate manganese phases, and calcium oxide and impurities such as silicon, aluminum, phosphorus, and lead generate silicates. If the calcination temperature is high, the composite ferrite and orthotitanate manganese will decompose to form more liquid phases, causing iron, titanium, and manganese to be lost in the locally generated liquid phase, thereby reducing the content of useful composite ferrite and orthotitanate manganese. If the calcination temperature is lower than 1200°C, due to incomplete solid phase reaction, especially the slow migration rate of titanium ions in the solid phase reaction of high melting point titanium dioxide, the orthotitanate content in the calcined sample is low and the phase crystallinity is poor.

[0019] The technical solution of the present invention adopts a two-stage method of preheating and roasting to control the generation of complex phase composite ferrite and orthotitanate and the regulation of impurity elements. First, the manganese source, strontium source, barium source, calcium source, etc. are decomposed into corresponding highly active metal oxides by the preheating process; when further roasted at a high temperature, iron, manganese, vanadium, strontium, and barium in an oxidized state will react to generate complex ferrite, while titanium, manganese, etc. will generate orthotitanate manganese, and calcium oxide and impurities silicon, aluminum, phosphorus, lead, etc. will generate silicate. The generation of silicate liquid phase can effectively prevent impurities from entering ferrite. Therefore, the generation of complex phase composite ferrite and orthotitanate can be effectively achieved through two-stage roasting, and the influence of impurities on the generation of composite ferrite can be avoided.

[0020] As a preferred solution, the ore is cooled to room temperature at a rate not exceeding 20°C / min in an air atmosphere. If the cooling rate is too fast, the solid phase reaction product will be incompletely crystallized, resulting in poor product performance. In addition, if the cooling rate is too fast, the minerals with extremely low crystallization rate in the roasted sample ore are easily condensed into a glass phase, and the presence of the glass phase affects the conversion of the composite ferrite and the improvement of its performance.

[0021] As a preferred solution, the fine grinding satisfies that the mass percentage of the -200 mesh particle size is 100%.

[0022] The present invention also provides an electromagnetic wave absorbing powder functional material, which is obtained by the above method. The electromagnetic wave absorbing powder functional material prepared by the present invention has good wave absorbing performance.

[0023] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0024] 1) The technical solution of the present invention can achieve the directional conversion of multi-metal components into composite ferrite and orthotitanate phases during the roasting process by rationally blending vanadium-titanium magnetite and ilmenite concentrates with manganese, strontium, barium, calcium, etc., while controlling the formation of liquid phase during the roasting process to promote the microscopic separation of impurity elements and target phases.

[0025] 2) The technical solution of the present invention is the first to use multi-metallic vanadium-titanium magnetite as a raw material to directly roast and prepare high-performance microwave-absorbing powder material, thereby realizing efficient value-added processing of complex and difficult-to-smelt vanadium-titanium magnetite.

[0026] 3) The technical solution of the present invention is simple to operate, low in cost, high in added value, and is conducive to industrial production.

[0027] 4) The technical solution of the present invention provides a new technology for the direct high-value utilization of vanadium-titanium magnetite. Compared with the existing blast furnace and non-blast furnace smelting processes for step-by-step extraction of iron, titanium and vanadium, the present invention has the following advantages: 1) All components can be utilized simultaneously; 2) No high-temperature smelting process is required. The technical solution of the present invention adopts oxidizing or inert atmosphere roasting, does not use coke, and has low greenhouse gas emissions; 3) Large quantities of high-performance magnetic wave-absorbing functional materials can be directly prepared with cheap mineral raw materials. DETAILED DESCRIPTION

[0028] The following examples are intended to further illustrate the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.

[0029] Example 1

[0030] The vanadium-titanium magnetite concentrate containing 56% TFe, 9.5% TiO2 and 0.65% V2O5 and the ilmenite concentrate containing 50% TFe and 21% TiO2 are used as raw materials, and manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide are used for ore blending and mixing to obtain a mixed material, wherein the grinding fineness of the vanadium-titanium magnetite, ilmenite concentrate, manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide raw materials all meet the mass percentage of -325 mesh size of 95%. The blending makes the mass ratio of (V+Sr+Ba+Mn) / Fe 0.55; the mass ratio of Ti / Mn 1.0; the mass ratio of CaO / SiO2 0.8; and the total iron content of the mixed material 48%. The mixed material is placed in a muffle furnace for preheating (nitrogen atmosphere) and roasting (air atmosphere), the preheating temperature is 600°C, the time is 60 minutes; the roasting temperature is 1200°C, the time is 240 minutes; the roasted sample is cooled with the furnace, and the cooling rate is 5°C / min. The cooled roasted sample is ground into -200 mesh particle size with a mass percentage of 100% by a ball mill, and a powder product with high electromagnetic wave absorption performance is obtained. The powder material has a reflectivity of -20dB to electromagnetic waves in the frequency range of 2 to 18GHz, and has excellent wave absorption performance, and can be used as a raw material for wave absorbing building materials.

[0031] Example 2

[0032] The vanadium-titanium magnetite concentrate containing 53% TFe, 10.5% TiO2 and 0.8% V2O5 and the ilmenite concentrate containing 52% TFe and 18% TiO2 are used as raw materials, and manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide are used for ore blending and mixing to obtain a mixed material, wherein the grinding fineness of the vanadium-titanium magnetite, ilmenite concentrate, manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide raw materials all meet the mass percentage of -325 mesh size of 100%. The ore blending makes the mass ratio of (V+Sr+Ba+Mn) / Fe be 0.85; the mass ratio of Ti / Mn be 0.65; the mass ratio of CaO / SiO2 be 0.5; and the total iron content of the mixed material be 45%. The mixed material is placed in a muffle furnace for preheating (nitrogen atmosphere) and roasting (air atmosphere), the preheating temperature is 950°C, the time is 10 minutes; the roasting temperature is 1350°C, the time is 30 minutes; the roasting sample is controlled to cool at a rate of 15°C / min. The cooled roasted sample is ground into -200 mesh size by a ball mill to obtain a powder product with high electromagnetic wave absorption performance. The powder material has a reflectivity of -18dB to electromagnetic waves in the frequency range of 2 to 18GHz, has excellent wave absorption performance, and can be used as a raw material for wave absorbing building materials.

[0033] Comparative Example 1

[0034] The mass ratio of (V+Sr+Ba+Mn) / Fe in this comparative example is low.

[0035] The vanadium-titanium magnetite concentrate containing 53% TFe, 10.5% TiO2 and 0.8% V2O5 and the ilmenite concentrate containing 52% TFe and 18% TiO2 are used as raw materials, and manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide are used for ore blending and mixing to obtain a mixed material, wherein the grinding fineness of the vanadium-titanium magnetite, ilmenite concentrate, manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide raw materials all meet the mass percentage of -325 mesh size of 100%. The blending makes the mass ratio of (V+Sr+Ba+Mn) / Fe 0.35; the mass ratio of Ti / Mn 0.65; the mass ratio of CaO / SiO2 0.5; and the total iron content of the mixed material 45%. The mixed material is placed in a muffle furnace for preheating (nitrogen atmosphere) and roasting (air atmosphere), the preheating temperature is 950°C, the time is 10 minutes; the roasting temperature is 1350°C, the time is 30 minutes; the roasting sample is controlled to cool at a rate of 15°C / min. The cooled roasted sample is ground into -200 mesh size with a mass percentage of 100% by a ball mill, and a powder product with electromagnetic wave absorption function is obtained. The powder material has a reflectivity of only -12dB to electromagnetic waves in the frequency range of 2 to 18 GHz, and the wave absorption performance is poor.

[0036] Comparative Example 2

[0037] The alkalinity in this comparative example is too high.

[0038] The vanadium-titanium magnetite concentrate containing 53% TFe, 10.5% TiO2 and 0.8% V2O5 and the ilmenite concentrate containing 52% TFe and 18% TiO2 are used as raw materials, and manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide are used for ore blending and mixing to obtain a mixed material, wherein the grinding fineness of the vanadium-titanium magnetite, ilmenite concentrate, manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide raw materials all meet the mass percentage of -325 mesh size of 100%. The ore blending makes the mass ratio of (V+Sr+Ba+Mn) / Fe 0.85; the mass ratio of Ti / Mn 0.65; the mass ratio of CaO / SiO2 1.2; and the total iron content of the mixed material 45%. The mixed material is placed in a muffle furnace for preheating (nitrogen atmosphere) and calcination (air atmosphere), the preheating temperature is 950°C, the time is 10 minutes; the calcination temperature is 1350°C, the time is 30 minutes; the calcination sample is controlled to cool at a rate of 15°C / min. The cooled calcined sample is ground into -200 mesh size with a mass percentage of 100% by a ball mill, and a powder product with electromagnetic wave absorption function is obtained. The powder material has a reflectivity of only -11dB to electromagnetic waves in the frequency range of 2 to 18 GHz, and the wave absorption performance is poor.

[0039] Comparative Example 3

[0040] The calcination temperature in this comparative example is relatively low.

[0041] The vanadium-titanium magnetite concentrate containing 53% TFe, 10.5% TiO2 and 0.8% V2O5 and the ilmenite concentrate containing 52% TFe and 18% TiO2 are used as raw materials, and manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide are used for ore blending and mixing to obtain a mixed material, wherein the grinding fineness of the vanadium-titanium magnetite, ilmenite concentrate, manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide raw materials all meet the mass percentage of -325 mesh size of 100%. The ore blending makes the mass ratio of (V+Sr+Ba+Mn) / Fe be 0.85; the mass ratio of Ti / Mn be 0.65; the mass ratio of CaO / SiO2 be 0.5; and the total iron content of the mixed material be 45%. The mixed material is placed in a muffle furnace for preheating (nitrogen atmosphere) and roasting (air atmosphere), the preheating temperature is 950°C, the time is 10 minutes; the roasting temperature is 1050°C, the time is 30 minutes; the roasting sample is controlled to cool at a rate of 15°C / min. The cooled roasted sample is ground into -200 mesh size by a ball mill to a mass percentage of 100%, thereby obtaining a powder product with electromagnetic wave absorption function. The powder material has a reflectivity of only -9dB to electromagnetic waves in the frequency range of 2 to 18 GHz, and has poor wave absorption performance.

[0042] Comparative Example 4

[0043] The titanium content of the mixed material in this comparative example is relatively low.

[0044] The vanadium-titanium magnetite concentrate containing 56% TFe, 9.5% TiO2 and 0.65% V2O5 and the ilmenite concentrate containing 50% TFe and 21% TiO2 are used as raw materials, and manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide are used for ore blending and mixing to obtain a mixed material, wherein the grinding fineness of the vanadium-titanium magnetite, ilmenite concentrate, manganese carbonate, calcium carbonate, strontium hydroxide and barium hydroxide raw materials all meet the mass percentage of -325 mesh size of 95%. The blending makes the mass ratio of (V+Sr+Ba+Mn) / Fe 0.55; the mass ratio of Ti / Mn 0.35; the mass ratio of CaO / SiO2 0.8; and the total iron content of the mixed material 48%. The mixed material is placed in a muffle furnace for preheating (nitrogen atmosphere) and roasting (air atmosphere), the preheating temperature is 600°C, the time is 60 minutes; the roasting temperature is 1200°C, the time is 240 minutes; the roasted sample is cooled with the furnace, and the cooling rate is 5°C / min. The cooled roasted sample is ground into -200 mesh size with a ball mill to a mass percentage of 100%, and a powder product with electromagnetic wave absorption function is obtained. The powder material has a reflectivity of only -9.5dB to electromagnetic waves in the frequency range of 2 to 18 GHz, and the wave absorption performance is poor.

Claims

1. A method for processing complex multi-metallic vanadium-titanium magnetite into functional materials, characterized by: Preheating, roasting, cooling and fine grinding a mixed powder material including vanadium-titanium magnetite and ilmenite concentrate, a manganese source, a calcium source, a strontium source and a barium source in sequence to obtain an electromagnetic wave absorbing powder functional material; The mixing ratio of vanadium-titanium magnetite, ilmenite concentrate, manganese source, calcium source, strontium source and barium source in the mixed powder satisfies: the mass ratio of (V+Sr+Ba+Mn) / Fe is between 0.55 and 0.85; the mass ratio of Ti / Mn is between 0.65 and 1.0; the mass ratio of CaO / SiO2 is between 0.5 and 0.8; the mass percentage of total iron is not less than 45%; The manganese source includes at least one of manganese carbonate, manganous oxide, manganese oxalate and manganese dioxide; The calcium source includes at least one of calcium carbonate, calcium oxide, calcium oxalate and calcium hydroxide; The strontium source includes at least one of strontium hydroxide, strontium oxide, and strontium oxalate; The barium source includes at least one of barium hydroxide and barium oxide.

2. The method for processing a complex multi-metallic vanadium-titanium magnetite functional material according to claim 1, characterized in that: The fineness of the mixed powder is such that the mass percentage of the -325 mesh particle size is not less than 95%.

3. The method for processing complex multi-metallic vanadium-titanium magnetite into functional materials according to claim 1, characterized in that: The preheating conditions are: in a nitrogen and / or inert gas atmosphere, at a temperature of 600° C. to 950° C., for 10 to 60 minutes.

4. The method for processing complex multi-metallic vanadium-titanium magnetite into functional materials according to claim 1, characterized in that: The calcination conditions are: calcination in air atmosphere at a temperature of 1200° C. to 1350° C. for 30 to 240 minutes.

5. The method for processing complex multi-metallic vanadium-titanium magnetite into functional materials according to claim 1, characterized in that: The cooling condition is: cooling to room temperature at a rate not exceeding 20° C. / min in an air atmosphere.

6. The method for processing complex multi-metallic vanadium-titanium magnetite into functional materials according to claim 1, characterized in that: The mass percentage of the fine grinding to meet the -200 mesh particle size is 100%.

7. An electromagnetic wave absorbing powder functional material, characterized in that: Obtained by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Vanadium recovery process

    CA3157393A1

  • A W-type ferrite electromagnetic-wave absorbent and the corresponding preparation method

    CN101217861A